Implementation of Law No. 12 of 1995 on Correctional Services in the Rehabilitation of Children - Gudur Yikwa; Kariadi Kariadi (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the child rehabilitation model implemented at the Class IIB Special Juvenile Rehabilitation Center (LPKA) and to assess the effectiveness of its implementation in shaping the personality and independence of juvenile inmates. The method used was empirical legal research, conducted at a Class IIB correctional facility with a population consisting of all juvenile inmates and a sample of three juvenile inmates. Data collection techniques included observation, interviews with juvenile inmates and correctional officers, and documentation. The data obtained were analyzed qualitatively by interpreting them into detailed and systematic descriptions, which were then discussed to draw inductive conclusions addressing the research questions. The novelty of this study lies in its direct examination of child rehabilitation practices based on empirical experience within correctional institutions. The results of the study indicate that the juvenile rehabilitation model at the Special Juvenile Correctional Institution is divided into two forms: character development and independence training. Character development includes group Dhuhr prayer, Islamic religious activities, catch-up education programs, morning exercises, and counseling sessions conducted by correctional facility mentors. The conclusion of this study confirms that the rehabilitation of children at the Special Juvenile Correctional Facility is generally structured through two main models, namely character development and independence training, which play a crucial role in the rehabilitation process and the shaping of juvenile inmates’ behavior.